1998
DOI: 10.1143/jjap.37.7015
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Secondary Electron Emission Coefficient (γ) of MgO Protective Layer with Various Crystallinities

Abstract: The secondary electron emission coefficient γ of a MgO protective layer with various crystallinities has been successfully measured by the γ-focused ion beam system with complete elimination of the charge accumulation problem by scanning-area adjustment techniques. It is found that the (111) surface has the highest γ from 0.14 to 0.26 in comparison with the other films with (200) and (220) crystallinities for operating Ne+ ions, while ranged from 0.03 to 0.24 for Ar+ ions, under operating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(33 citation statements)
references
References 4 publications
2
30
0
Order By: Relevance
“…[1][2][3][4] To display dynamic images using AC-PDPs, a firing voltage is applied to the electrodes to initiate discharge. Then, ultraviolet photons emitted from the plasma are absorbed in phosphors, and visible photons are generated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] To display dynamic images using AC-PDPs, a firing voltage is applied to the electrodes to initiate discharge. Then, ultraviolet photons emitted from the plasma are absorbed in phosphors, and visible photons are generated.…”
Section: Introductionmentioning
confidence: 99%
“…5 Improving the performance of AC-PDPs and reducing the firing voltage of plasma (Vf) is essential, and can be achieved by using a protective layer with a higher ion-induced secondary electron (IISE) yield, γ. Therefore, γ is one of the most important parameters of the MgO protective layer for improving the discharge characteristics, 1,6 and the IISE phenomenon in MgO films has been intensively studied. [7][8][9][10][11][12][13][14][15] The magnitude of γ is strongly influenced by the MgO film electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…24). The experimental results showed that the surface composition and the surface morphology significantly influence the SEE coefficient [184,185]. Lee et al [102] found that the magnitude of the SEE yield of the MgO film strongly depends to the detailed mechanisms of electron supply, which is determined by the applied bias voltage to the sample.…”
Section: Secondary Electron Emission Yieldmentioning
confidence: 99%
“…Beside these chemical reactions at the YSZ|plasma interface, emission effects can take place. According to the literature, the coefficient for secondary electron emission of an oxide can be higher than for the corresponding metal [14,15]. Furthermore, the field-assisted emission of O − ions from the surface of YSZ into vacuum has been reported in the literature, the details of the mechanism are subject to disussion [16].…”
Section: Introductionmentioning
confidence: 99%